Stone disease in low‐ and middle‐income countries: could augmented reality have a role in its management?. (6th September 2022) - Watson, Graham; Payne, Stephen R.; Kunitsky, Kevin; Natchagande, Gilles; Mabedi, Charles; Scotland, Kymora B.
Abstract: Urolithiasis is a global phenomenon. Cystolithiasis is common in parts of Africa due to low protein intake and dehydration from endemic diarrhoeal illnesses. Nephrolithiasis is less prevalent than in high‐income countries, probably due to a variety of lifestyle issues, such as a more elemental diet, higher physical activity, and less obesity. Although renal stones are less common in low‐ and middle‐income countries (LMICs), the social and economic impacts of nephrolithiasis are still considerable; many stones present late or with complications such as upper urinary tract obstruction or urosepsis. These may lead to the development of chronic kidney disease, or end‐stage renal failure in a small proportion of cases, conditions for which there is very poor provision in most LMICs. Early treatment of nephrolithiasis by the least invasive method possible can, however, reduce the functional consequences of urinary stone disease. Although extracorporeal lithotripsy is uncommon, and endoscopic interventions for stone are not widespread in most of Africa, percutaneous nephrolithotomy and ureteroscopic renal surgery are viable techniques in those regional centres with infrastructure to support them. Longitudinal mentoring has been shown to be a key step in the adoption of these minimally invasive procedures by local surgeons, something that has been difficult during the coronavirus disease 2019 (COVID‐19) pandemic due to travel restriction. Augmented reality (AR) technology is an alternative means of providing remote mentoring, something that has been trialled by Urolink, the MediTech Trust and other global non‐governmental organisations during this period. Our preliminary experience suggests that this is a viable technique for promulgating skills in LMICs where appropriate connectivity exists to support remote communication. AR may also have long‐term promise for decreasing the reliance upon short‐term surgical visits to consolidate competence, thereby reducing the carbon footprint of global surgical education.